Perlindungan Hukum Terhadap Pengguna Jasa PT. Telkom - Tri Noviastanti, Selly; Munandar, Aris (Faculty of Law, University of Mataram, 2024)
This study aims to determine consumer protection for service users of Telkom Ltd subscribes to Indihome products. This research is normative and empirical legal research. Data collection was obtained by field library research by conducting direct interviews with the parties involved and by using statutory, sociological, and contextual approaches. The data that is processed as a source is primary and secondary data. The results of this study conclude that the legal relationship between IndiHome service users and Telkom Ltd is trading in IndiHome services and legal protection for users of IndiHome internet network services provided by Telkom Ltd is basically protected, because the rights of service users have been granted.